2017
DOI: 10.1111/ahe.12274
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Immunohistochemical Staining in the Porcine Ovary

Abstract: This study aimed to investigate leptin immuno-staining of the porcine ovary in different reproductive stages. Ovaries from 21 gilts were collected from slaughterhouses. The ovarian tissue sections were incubated with a polyclonal anti-leptin as a primary antibody. The immuno-staining in ovarian tissue compartments was calculated using imaging software. Leptin immuno-staining was found in primordial, primary, preantral and antral follicles. Leptin immuno-staining was expressed in the oocyte and granulosa and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Furthermore, plasma leptin concentrations were higher in sows with high BF thickness ( >24 mm) compared to sows with moderate (16–24 mm) and low BF thickness (<16 mm). A recent morphological study has confirmed that leptin exists in different compartments of porcine ovary, including the oocyte, granulosa cells, and corpus luteum, which indicated a close relationship between leptin and ovarian function in pig [23]. These findings indicate that the response of sow to GnRH treatment is associated with excessive loss of body weight and BF thickness during lactation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, plasma leptin concentrations were higher in sows with high BF thickness ( >24 mm) compared to sows with moderate (16–24 mm) and low BF thickness (<16 mm). A recent morphological study has confirmed that leptin exists in different compartments of porcine ovary, including the oocyte, granulosa cells, and corpus luteum, which indicated a close relationship between leptin and ovarian function in pig [23]. These findings indicate that the response of sow to GnRH treatment is associated with excessive loss of body weight and BF thickness during lactation.…”
Section: Discussionmentioning
confidence: 82%
“…Sows with poor BCS at weaning had smaller follicles and longer WOI compared to sows with BCS of more than 2 [4]. Backfat is an essential source of estrus cycle-related hormones, such as insulin-like growth factor-1 (IGF-1) [24] and leptin [9], which is necessary for the production of reproductive hormone that is associated with granulosa cell proliferation and oocyte development [23, 25]. Moreover, in the present study, we found that sows that were not responding to GnRH treatment (IOI >68 hr) had lower BF than those that ovulated before 68 hr (13.8 mm vs. 14.9–16.4 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, leptin and LEPR proteins were reported in granulosa cells during all stages of goat follicular development (Batista et al, 2013). Additionally, leptin immunostaining was also found in granulosa cells, theca interna cells and luteal cells in swine (Phoophitphong et al, 2017). Therefore, the presence of a leptin signaling system in the ovary suggests that it could be involved in the ovarian function in sheep.…”
Section: Discussionmentioning
confidence: 97%
“…In knockout of G Gαq/11 in mouse granulosa cells, LHR failed to fully induce the expression of the progesterone receptor (PGR), resulting in follicular rupture defects (Breen et al, 2013). Interestingly, the Gαq signal was similar to LHR in oocytes and testes (Yung et al, 2014;Phoophitphong et al, 2017), suggesting that gnaq has a potential function in follicular rupture and testis development-although he nature of this is unclear. On the other hand, gnaq was located in secretory cells, as was GnRH (Tsai, et al, 2003).…”
Section: Discussionmentioning
confidence: 99%